The effect of hydronium ions on the structure of phospholipid membranes - Deplazes, Evelyne; Poger, D.; Cornell, B.; Cranfield, C. (R S C Publications, 2017)
This work seeks to identify the mechanisms by which hydronium ions (H 3 O + ) modulate the structure of phospholipid bilayers by studying the interactions of H 3 O + with phospholipids at the molecular level. For this, we carried out multiple microsecond-long unrestrained molecular dynamics (MD) simulations of a POPC bilayer at different H 3 O + concentrations. The results show that H 3 O + accumulates at the membrane surface where it displaces water and forms strong and long-lived hydrogen bonds with the phosphate and carbonyl oxygens in phospholipids. This results in a concentration-dependent reduction of the area per lipid and an increase in bilayer thickness. This study provides an important molecular-level insight into the mechanism of how H 3 O + modulates the structure of biological membranes and is a critical step towards a better understanding of the effect of low pH on mammalian and bacterial membranes.